(untitled) (World Bulletin of Education and Learning, 2026)
This article examines the methodological possibilities for developing speech activity in foreign language teaching through a psycholinguistic approach within inclusive education. The relevance of the study is determined by the growing need to create flexible, learner-centered, and psychologically grounded teaching strategies that support students with diverse cognitive, linguistic, sensory, and communicative needs. In inclusive foreign language classrooms, speech activity is not limited to the mechanical reproduction of vocabulary or grammar; it involves perception, comprehension, internal speech, motivation, emotional readiness, memory, attention, and social interaction. Therefore, the psycholinguistic approach provides a scientific basis for understanding how learners process foreign language input, transform it into meaningful communication, and gradually develop productive speech skills. The article highlights the importance of adapting foreign language instruction to individual psycholinguistic characteristics of learners, including speech tempo, language anxiety, auditory perception, verbal memory, and communicative motivation. Special attention is given to methodological tools such as dialogic exercises, visual-verbal support, situational speech tasks, multisensory learning, role-play, scaffolding, and differentiated feedback. These methods help create a supportive educational environment where each learner can participate in communication according to his or her abilities. The study argues that the development of speech activity in inclusive education requires integration of linguistic, psychological, pedagogical, and social factors. The psycholinguistic approach enables teachers to identify barriers to speech production and to design appropriate corrective, developmental, and communicative tasks. As a result, foreign language teaching becomes more accessible, emotionally comfortable, and effective for learners with different educational needs.